Optimizing Kidney Disease Management during Ramadan: Evidence-Based Risk Stratification and Tailored Strategies - Sourabh Sharma,; Manisha Sahay,; Mastakim Ahmed Mazumder,; Sanjay Kalra, (Journal of the Pakistan Medical Association, 2025)
Fasting during Ramadan poses distinct challenges forindividuals with kidney disease, requiring a careful balancebetween spiritual commitments and health maintenance.This article combines insights from recent research andguidelines to offer a thorough framework for riskassessment. Patients are classified into low, moderate, andhigh-risk categories based on individual, environmental,and health-related factors. Management approaches areorganized into four main areas: spiritual support, non-druginterventions, medication adjustments, and modificationsto kidney replacement therapy (KRT). Evidence indicatesthat stable chronic kidney disease (CKD) patients, especiallythose in stages 1–3, and kidney transplant recipients withstable graft function can fast safely with carefulsupervision. Conversely, patients with advanced CKD, thoseon dialysis, and individuals with significant additionalhealth issues are advised against fasting due to possiblecomplications. Essential recommendations includeoptimizing hydration, customizing medication plans,conducting regular monitoring, and making dietaryadjustments. By merging medical knowledge with culturalawareness, healthcare providers can facilitate safe fastingand enhance health outcomes during Ramadan. Keywords: Ramadan, Chronic kidney disease, Religion,Fasting, Dialysis